Food handling practices among street food vendors and their associated factors in the town administration of Gamo Zone, Southern Ethiopia - Girma, Zeleke; Temesgen, Kidus; Dubale, Amanuel; Waritu, Nuredin Chura; Jemal, Mohammed; Wakeyo, Mamud Umer (Frontiers in Food Science and Technology, 2025)
IntroductionFood handling practice is a serious issue that can increase the risk of contracting foodborne illnesses unless it is well-practiced by street food vendors. Food sold on the street is currently very popular in Ethiopia and is contaminated with various sources of infections due to the poor handling practices of street food vendors that can cause foodborne illnesses. However, there has been little research on the food handling practices of street food vendors in the Gamo zone. Thus, we aimed to assess food handling practices among street food vendors and their associated factors in the town administration of the Gamo Zone.MethodsA cross-sectional study design was conducted from October to December 2021. A simple random sampling technique by the lottery method was used to select 421 participants. The data were collected through interviews and observations, entered into EpiData version 7, and transported to STATA version 13 for analysis by logistic regression. Statistical significance was set at p < 0.05.Results and discussionThe magnitude of good food handling was 40%. Male gender [AOR = 7.03, 95% CI: 3.36–14.71], ages 19–25 [AOR = 9.34, 95% CI: 3.11–28.07] and 26–35 [AOR = 4.80, 95% CI: 1.54–14.99], married participants [AOR = 6.48, 95% CI: 1.69–24.89], college diploma and above [AOR = 5, 95% CI: 1.46–23], monthly income of 1,001–2,000 ETB [AOR = 3.46, 95% CI: 1.50–7.96], and availability of hand washing facility [AOR = 2.68, 95% CI: 1.24–5.77] were significant predictors of good food handling practices.ConclusionAbove half of the food vendors had poor food handling practices. Gender, ages, marital and educational status, monthly income, and handwashing facility were factors associated with food handling practice. Therefore, improving the monthly income and educational status of the food handlers, counseling, and periodic inspections may improve their good food handling practices.